A new species of the genus Crepidodera Chevrolat (Coleoptera: Chrysomelidae) from Baltic amber - Bukejs, Andris (Zootaxa, 2014)
A new flea-beetle species, Crepidodera svetlanae sp. nov. (Coleoptera: Chrysomelidae: Galerucinae: Alticini) is described and illustrated from the Baltic amber. The new species is compared with the fossil and recent species of the genus. A key to species of flea beetles known from fossil resin is provided.